The Identity Crisis of Jeng Yah in the “Gadis Kretek” Movie: The Study of Erick H. Erikson's Developmental Psychology - Jannah, Anis Faikatul; Raras Hafiidha Sari (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The study aims to analyze the identity crisis conflicts of Jeng Yah characters in the film "Kretek Girl" using the approach of developmental psychology of Erik H. Erikson. The method used is a qualitative approach, by choosing the movie "Kreta Girl" as the object of research and analyzing the character of Jang Yah based on the theory of personality development of Erickson. Hopefully, this research could make a significant contribution to understanding the personality psychology of the characters in the film, as well as be a reference for future researchers in analyzing the character in the context of developmental psychology. Thus, this research is expected to provide a deeper insight into the complexity of human personality and how it is reflected in media representations like movies.